A high‐resolution genetic map of the cereal crown rot pathogen Fusarium pseudograminearum provides a near‐complete genome assembly. (25th January 2017) - Gardiner, Donald M.; Benfield, Aurelie H.; Stiller, Jiri; Stephen, Stuart; Aitken, Karen; Liu, Chunji; Kazan, Kemal
Summary: Fusarium pseudograminearum is an important pathogen of wheat and barley, particularly in semi‐arid environments. Previous genome assemblies for this organism were based entirely on short read data and are highly fragmented. In this work, a genetic map of F. pseudograminearum has been constructed for the first time based on a mapping population of 178 individuals. The genetic map, together with long read scaffolding of a short read‐based genome assembly, was used to give a near‐complete assembly of the four F. pseudograminearum chromosomes. Large regions of synteny between F. pseudograminearum and F. graminearum, the related pathogen that is the primary causal agent of cereal head blight disease, were previously proposed in the core conserved genome, but the construction of a genetic map to order and orient contigs is critical to the validation of synteny and the placing of species‐specific regions. Indeed, our comparative analyses of the genomes of these two related pathogens suggest that rearrangements in the F. pseudograminearum genome have occurred in the chromosome ends. One of these rearrangements includes the transposition of an entire gene cluster involved in the detoxification of the benzoxazolinone (BOA) class of plant phytoalexins. This work provides an important genomic and genetic resource for F. pseudograminearum, which is less well characterized than F. graminearum . In addition, this study provides new insights into a better understanding of the sexual reproduction process in F. pseudograminearum, which informs us of the potential of this pathogen to evolve.